1995
DOI: 10.1074/jbc.270.33.19294
|View full text |Cite
|
Sign up to set email alerts
|

The Affinity of Pyridoxal 5′-Phosphate for Folding Intermediates of Escherichia coli Serine Hydroxymethyltransferase

Abstract: Escherichia coli serine hydroxymethyltransferase is a 94-kDa homodimer. Each subunit contains a covalently attached pyridoxal-P, which is required for catalytic activity. At which step pyridoxal-P binds in the folding pathway of E. coli serine hydroxymethyltransferase is addressed in this study. E. coli serine hydroxymethyl-transferase is rapidly unfolded to an apparent random coil in 8 M urea. Removal of the urea initiates a complete refolding to the native holoenzyme in less than 10 min at 30 degrees C. Seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 25 publications
5
65
0
Order By: Relevance
“…This finding may indicate that electrostatic interactions play a significant role in the stabilization of the dimer. The ⌬G of the monomer secondary structure unfolding is below the lowest limit reported for many globular proteins from mesophiles, whereas the transition midpoint is at 2.56 M denaturant, a value similar to that reported for the dimeric E. coli enzyme at neutral pH (41). This fact indicates that the monomeric protein can tolerate high concentrations of denaturant without showing a remarkable conformational stability at 20°C.…”
Section: Resultsmentioning
confidence: 54%
“…This finding may indicate that electrostatic interactions play a significant role in the stabilization of the dimer. The ⌬G of the monomer secondary structure unfolding is below the lowest limit reported for many globular proteins from mesophiles, whereas the transition midpoint is at 2.56 M denaturant, a value similar to that reported for the dimeric E. coli enzyme at neutral pH (41). This fact indicates that the monomeric protein can tolerate high concentrations of denaturant without showing a remarkable conformational stability at 20°C.…”
Section: Resultsmentioning
confidence: 54%
“…7, a and b) exhibit a different composition of secondary structure elements for apo-compared with holo-OASS. In contrast, other PLP-dependent enzymes, including serine hydroxymethyltransferase (39,40), mitochondrial aspartate aminotransferase (41) (fold type I), and tryptophan synthase (42) (fold type II), exhibit similar spectra for the apo-and holoenzyme. Despite the well known uncertainty in the quantitative evaluation of secondary structure content from CD spectra, the calculated values for holo-OASS are in good agreement with the crystallographic data (Table II).…”
Section: Discussionmentioning
confidence: 99%
“…The addition of glycine and H 4 PteGlu to every SHMT that has been studied results in an abortive complex that absorbs near 500 nm, which is characteristic of a quinonoid structure known to be on the catalytic pathway. However, the Pro 258 and Pro 264 mutants do not give this complex with glycine and H 4 PteGlu, suggesting that they are blocked in going from the external aldimine to the quinonoid intermediate. A previous study of sheep liver SHMT also showed that the P297R mutant (equivalent to Pro 258 ) resulted in the loss of 85% of its activity (23).…”
Section: Role Of Promentioning
confidence: 99%
“…Double reciprocal plots of initial velocity versus serine concentration was used to determine K m and k cat values with saturating levels of H 4 PteGlu (0.2 mM) used as the cosubstrate. The K d for H 4 PteGlu was determined by a spectrophotometric method involving the formation of an abortive complex with glycine that absorbs uniquely at 495 nm (10). Saturating levels of glycine (50 mM) were used, and the absorbance at 492 nm of the SHMT⅐Gly⅐H 4 PteGlu abortive complex was determined as a function of increasing concentrations of H 4 PteGlu.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation